Glycerol enhances fungal germination at the water-activity limit for life - Stevenson, Andrew; Hamill, Philip G.; Medina, Angel; Kminek, Gerhard; Rummel, John D.; Dijksterhuis, Jan; Timson, David J.; Magan, Naresh; Leong, Su-lin L.; Hallsworth, John E. (Wiley, 2016)
For the most-extreme fungal xerophiles, metabolic activity and cell division typically halts between 0.700 and 0.640 water activity (approximately 70.0-64.0% relative humidity). Here, we investigate whether glycerol can enhance xerophile germination under acute water-activity regimes, using an experimental system which represents the biophysical limit of Earth's biosphere. Spores of a variety of species including Aspergillus penicillioides, Eurotium halophilicum, Xerochrysium xerophilium (formerly Chrysosporium xerophilum), and Xeromyces bisporus, were produced by cultures growing on media supplemented with glycerol (up to 189 mg glycerol g dry spores−1). The ability of these spores to germinate and their kinetics of germination were then determined in media designed to recreate stresses experienced in microbial habitats or anthropogenic systems (water-activities from 0.765-0.575). For A. penicillioides, E. amstelodami, E. halophilicum, X. xerophilium and X. bisporus, germination occurred at lower water-activities than previously recorded (0.640, 0.685, 0.651, 0.664 and 0.637 respectively). In addition, the kinetics of germination at low water-activities were substantially faster than those reported previously. Extrapolations indicated theoretical water-activity minima below these values; as low as 0.570 for A. penicillioides and X. bisporus. Glycerol is present at high concentrations (up to molar levels) in many types of microbial habitat. We discuss the likely role of glycerol in expanding the water-activity limit for microbial function in relation to temporal constraints and location of the microbial cell or habitat. The findings reported here also have critical implications for understanding the extremes of Earth's biosphere; for understanding the potency of disease-causing microorganisms; and in biotechnologies that operate at the limits of microbial function. This article is protected by copyright. All rights reserved.